Features of the memory of teens (Actual Problems of Psychology in Educational Institutions, 2012)
The article presents the results of studying the peculiarities ofmemory in adolescents. It is established that in the adolescence, logical memoryis actively developing. It also rapidly reaches the level that the child moves tothe predominant use of this type of memory, and arbitrary and mediatedmemory. Considered what type of memory prevails in adolescence. The firstpart contains general information about a teenager, about changes in memory. Inthe second part, the memory of a teenager was investigated. It is concluded thatin the adolescents the level of mechanical memory is gradually decreasing and,accordingly, the speed of logical memory increases.
Keywords: memory, teenager, mechanical memory, logical memory